Species Composition and Diversity of Zooplankton in Chackferi Stream, Tarai Region, Uttarakhand, India - Ranjeeta; Mehra, Rajni (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Present study deals with the analysis of species composition and diversity of zooplankton in Chackferi stream. For this investigation samples were collected by monthly intervals for a period of September 2020 to August 2022. A total of 28 species of zooplankton, belonging to 25 genera across 5 groups were identified such as Protozoa (6 species of 6 genera), Rotifera (10 species of 9 genera), Copepoda (7 species of 5 genera), Cladocera (3 species of 3 genera) and Ostracoda (2 species of 2 genera). Rotifera was the dominant group, comprising (36%) of the zooplankton community in Chackferi stream, followed by Copepoda (25%), Protozoa (21%), Cladocera (11%) and Ostracoda (7%). It was noticed that seasonal composition of zooplankton was highest during summer, moderate in winter and autumn and least in monsoon season. Zooplankton are also considered as a good bio-indicator to assess the pollution status of a stream. Presence of indicator species like Brachionus calyciflorus, Brachionus falcatus and Mesocyclops leuckarti reveals that the stream gets organically polluted and rapidly moving toward a eutrophic condition. Therefore, frequent monitoring and proper treatment should be applied for conservation of the stream and its ecosystem.